Edukasi Kesehatan Mengenai Pencegahan Gastroenteritis Akut (GEA) di Rumah Sakit Bintang Amin - Rika Yulendasari; Benny Gustian; Vitarostiawati Vitarostiawati; Haris Safari; Andi Apriyansyah; Erin Eca Lorenza; Martina Eka Santi; Insia Insia (Natural: Jurnal Pelaksanaan Pengabdian Bergerak bersama Masyarakat., 2025)
Globally, the World Health Organization (WHO) notes that diarrhea related to acute gastroenteritis (AGE) is the second leading cause of death in children under five years of age, with more than 1.7 billion cases of diarrhea occurring each year. The economic burden due to AGE is substantial, including healthcare costs, loss of productivity, and long-term impacts on nutrition status and child development. Objective: to increase public awareness regarding the prevention of AGE. Method: The health education activities were conducted in the inpatient room of Bintang Amin Hospital using the method of community service by providing education on AGE prevention. The participants of the counseling were patients and their families. Results: This activity was held on Saturday, June 14, 2025, at Bintang Amin Hospital. All respondents were very enthusiastic about the material and demonstrations presented. Conclusion: After the counseling on the prevention of GEA, there was an increase in knowledge among respondents as seen from their responses when asked about the concept of GEA disease.